NILAI MORAL DALAM TIGA CERITA PENDEK â€œIN THE CEMETERY WHERE AL JOLSON IS BURIEDâ€, â€œTHE SHAWLâ€, DAN â€œEMERGENCYâ€ - KAMURAHANG, TUN REYNALDI ZAKRI; SIGARLAKI, STEPHANI J.; PAMANTUNG, RINA P. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTÂ Â Â  This research entitled â€œ Nilai-Nilai Moral Dalam Cerita Pendek Kontemporer â€œIn the Cemetery Where Al Jolson is Buriedâ€ Karya Amy Hempel, â€œThe Shawlâ€ Karya Cynthia Ozick, dan â€œEmergencyâ€ Karya Denis Jhonsonâ€. The statements of problem of this research are what the moral values in three of the contemporary short stories and how the moral values depicted on the contemporary short stories.The objectives of this research are to identify and classify the moral values in three of the contemporary short stories and to describe and analyze the moral values in three of the contemporary short stories. This research uses extrinsic and intrinsic method.The data of Moral Values are collected from sentences acts of characters in the short stories and analyzed according to Sulistyorini (2011),Claraence (1973), and Stanton (1965).The result of this research shows that there are two types of moral values in the contemporary short stories, there are individual and social moral values. The individual moral values those are appreciate and respect, hard work, wise, and integrity. The social moral values those are care about the other people, the giver of advice, work together, and affection.Keywords: Moral Values, Short Stories, Contemporer.